The Analysis of Students’ Design Thinking in Inquiry-Based Learning in Routine University Science Courses - Prayogi, Saiful; Ardi, Raden Fanny Printi; El Yazidi, Rachid; Tseng, Kuang-Chih; Mustofa, Hisbulloh Als (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2023)
Design thinking has garnered widespread recognition for its distinctive problem-solving and innovative approach, attracting the attention of both professionals and academics. It has expanded beyond its origins in the design field and is now being applied in diverse domains. This article focuses on the integration of design thinking into science education, particularly within the framework of inquiry-based learning. To comprehensively explore the study objectives, a mixed methods approach involving both quantitative and qualitative methods was employed. The study included 102 first-year university students enrolled in science courses. The assessment of students' design thinking dimensions is conducted using instruments that have been rigorously validated and proven to be reliable in terms of their psychometric properties. The findings revealed that students exposed to inquiry-based learning demonstrated significant improvements in their design thinking skills compared to those taught through conventional methods. Furthermore, interviews with lecturers provided additional support for the positive impact of inquiry-based learning on students' design thinking abilities.